2014
DOI: 10.1038/ismej.2014.236
|View full text |Cite
|
Sign up to set email alerts
|

Adult blood-feeding tsetse flies, trypanosomes, microbiota and the fluctuating environment in sub-Saharan Africa

Abstract: The tsetse fly vector transmits the protozoan Trypanosoma brucei, responsible for Human African Trypanosomiasis, one of the most neglected tropical diseases. Despite a recent decline in new cases, it is still crucial to develop alternative strategies to combat this disease. Here, we review the literature on the factors that influence trypanosome transmission from the fly vector to its vertebrate host (particularly humans). These factors include climate change effects to pathogen and vector development (in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 109 publications
1
35
3
Order By: Relevance
“…Although a decrease in plant and animal diversity with increasing elevation is a widely documented pattern in ecology, it has been suggested that the biogeographical patterns exhibited by bacteria may be fundamentally different from those of plants and animals [79]. Our findings do not support this hypothesis but are in line with the idea that microbiota diversity decreases with increasing distance from the host’s environmental optimum, such as at a host’s range edge or during torpor [80]. Similarly, we observed changes in microbial beta diversity with elevation, particularly in female ticks, and a significantly larger group dispersion in microbial beta diversity at lower elevations.…”
Section: Discussioncontrasting
confidence: 76%
“…Although a decrease in plant and animal diversity with increasing elevation is a widely documented pattern in ecology, it has been suggested that the biogeographical patterns exhibited by bacteria may be fundamentally different from those of plants and animals [79]. Our findings do not support this hypothesis but are in line with the idea that microbiota diversity decreases with increasing distance from the host’s environmental optimum, such as at a host’s range edge or during torpor [80]. Similarly, we observed changes in microbial beta diversity with elevation, particularly in female ticks, and a significantly larger group dispersion in microbial beta diversity at lower elevations.…”
Section: Discussioncontrasting
confidence: 76%
“…We reported infections between 26° C to 36° C with the highest infection rates at around 31° C. There could be two reasons for this observation; first, there is the rapid differentiation and proliferation of trypanosome species at temperatures between 26° C and 37° C as suggested by laboratory studies; second, nutritional stress could affect these patterns where high temperatures induced quick digestion of blood meals in the tsetse fly leading to more frequent feeding events, and hence increased risk of infection. Other exo‐endogenous factors might also play an important role, such as quality of blood source, type of tsetse fly midgut enzymes, and quality of parasite surface coat, though they were beyond the scope of this study (Kubi 2006, Akoda et al , Geiger et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The colonization of the gut by microbial communities may or may not increase tsetse fly resistance against trypanosome invasion. Previous work suggests that Sodalis and Wigglesworthia (both maternally transmitted symbionts of tsetse flies) can modulate trypanosome development 22 . Wigglesworthia must be present in the larval stage during the maturity of tsetse flies for their immune system to properly develop and function 23 .…”
mentioning
confidence: 99%